Association between the use of analgesics and doping - A survey in 2,997 triathletes - Dietz, P.; Dalaker, R.; Letzel, S.; Ulrich, R.; Simon, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: According to several epidemiological studies, the use of doping substances has been reported to be common practice among competitive athletes (Dietz et al., 2013; Striegel et al., 2010). Further studies showed that non-prohibited physical performance-enhancing substances, such as nutritional supplements (NS), provide a gateway for using doping substances (Backhouse et al., 2013). Additionally, the use of non-steroidal anti-inflammatory drugs (NSAIDs), including over-the-counter (OTC) analgesics, directly before a competition, has also been reported to be common use among endurance athletes such as marathon runners (Kuster et al., 2013) and triathletes (Gorski et al., 2011). The objective of this study was to test whether the use of analgesics is associated with the use of doping and therefore provides a gateway to doping as discussed for NS. Methods: A questionnaire primarily addressing the use of analgesics and doping was distributed among 2,997 triathletes. The randomized response technique (RRT) was used to estimate the 12-month prevalence of doping in order to assess whether users of analgesics have a higher potential risk for doping than non-users. Statistical power analyses were performed to determine sample size. The bootstrap method was used to assess the statistical significance of the prevalence difference for doping between users and nonusers of analgesics. Results: The 12-month prevalence estimate for the use of doping substances (overall estimate 13.0%) was significantly higher in athletes that used analgesics (20.4%) than in those athletes who did not use analgesics (12.4%). Discussion: The results of this study revealed that athletes who use analgesics prior to competition may be especially prone to using doping substances. As a practical implication of the present findings, we recommend athletes and coaches to handle the consumption of analgesics with care, and only use them for therapeutic reasons instead of pain prevention.